Biochemical changes in caprine granulosa cells: Relation to follicle size and stage of cyclicity - SANGHA, G K; KHERA, K S; BHATIA, H (The Indian Journal of Animal Sciences, 2011)
Granulosa cells from small (<2 mm), medium (3–5 mm), and large (>5 mm) follicles were harvested aseptically from the ovaries of immature and mature goats in various stages of estrous cycle. The cells were separated by centrifugation from follicular fluid. Total proteins and enzymatic activities were biochemically determined in granulosa cells by standard methods. Total protein content increased from small to large follicles in all categories in granulose cells. Acid phosphatase (ACP) activity decreased with increase in follicular size. Alkaline phosphatase (ALP) activity decreased in medium follicles but showed an increase in large follicles, except during luteal phase where a continuous increase in the activity with the growth of the follicle was observed. In both immature and mature animals, the lactate dehydrogenase (LDH) activity decreased in the granulosa cells of medium sized follicles but increased significantly in large follicles. 3ßhydroxy steroid dehydrogenase (3ß-HSDH) showed an abrupt increase in its activity in granulosa cells of large follicles. The activity of this enzyme was more in luteal phase of cyclicity. The changes in the biochemical constituents may be correlated with the different biosynthesizing potential of the granulosa cells of maturing follicles during different stages of estrous cycle.